Symmetry versus Asymmetry in a Fixed Exchange Rate System - Timothy D. Lane; Daniel Gros (Kredit und Kapital, 1994)
Symmetry vs. Asymmetry in einem festen Wechselkurssystem Mit dem Übergang vom Europäischen Währungssystem (EWS) zur Europäischen Währungsunion (EWU) wird ein asymmetrisches System (das EWS) durch ein symmetrisches (die EWU) ersetzt. Im Rahmen eines analytischen Zweiländermodells untersucht der vorliegende Beitrag daher die Auswirkungen von Schocks auf die beteiligten Länder in symmetrischen und asymmetrischen Währungssystemen. Diese Analyse zeigt, daß der Wegfall der noch bestehenden Handelshemmnisse durch das Binnenmarktprogramm, sowie der durch die Wiedervereinigung ausgelöste Schock, den Übergang zu einem symmetrischen System (also der EWU) attraktiver macht. – – Moving from the European Monetary System (EMS) to a European Monetary Union (EMU) implies a move from an asymmetric to a symmetric currency system. This paper uses a simple two-country model to compare the impact of various shocks on each country's economy under alternative monetary arrangements, providing a basis for comparing symmetric and asymmetric systems and permitting an interpretation of the member countries' divergent interests and the resulting Nash equilibrium. The analysis implies that the removal of trade barriers through the European Single Market plan and the additional shocks associated with German unification may partly explain the recent move toward a symmetrical system.
Keywords: 330